Factors Affecting Shopee Behavioural Intention for Indonesian Low-Income Users - Evan Taruna; Michael Valentino (iBuss Management, 2022)
The Covid Pandemic has impacted Indonesian’s shopping behaviors from offline into online shopping as the rise of m-commerce platforms such as Shopee provides services for their users to transact online. Research done by Dakduk et al. (2020) seek to understand the factors that influence low-income m-commerce users to transact online using m-commerce in an emerging country, Ecuador. Therefore, this research aims to apply the same framework in Indonesia specifically on Shopee. The framework used in Dakduk et al. (2020) research contained seven independent constructs: performance expectancy, social influence, facilitating conditions, habit, hedonic motivations, perceived security, and perceived trust. This research used quantitative method by using simple random sampling and online questionnaires to collect low-income Shopee users in Indonesia. PLS-SEM and bootstrapping method were used to analyzed 100 respondents’ answers. This research founds out that facilitating conditions, habit, hedonic motivation, and perceived trust relationships to behavioral intention were significant while performance expectancy, social influence, and perceived security were not.Keywords: Financial technology adoption, Performance expectancy, Social influence, Facilitating conditions, Hedonic motivation, Habit, Perceived trust, Perceived Security, Unified Theory of Acceptance and Use of Technology, Shopee, Indonesian low-income users